ANALYSIS OF THE MAIN TRENDS IN THE BRAZILIAN YOGURT MARKET - Stecca Caires da Silva, Isadora; Claudio Pandolfi, Marcos Alberto (Revista Interface Tecnológica, 2020)
Yogurt is a significant segment inside the Brazilian food sector. Having as your main raw material, the milk that is a important part for the country agribusiness, along with the fermentation of bacteria like Streptococcus thermophillus and Lactobacillus bulgaricus. In the lapse of the years there was a significant increase in demand for the product and this fact is due to the diversity of segments that it offers, it can be consumed since the breakfast, as well to culinary and even to pets. There are diversities of types and flavors, but according to researches, the strawberry flavor is the most consumed, having low calories and being rich in nutrients. Estimatives until 2026, are that this market will only grow, becoming even more competitive, because being considered as healthy product, the yogurt is part of approximately 50% of the feeding of a population that today choose for a healthy and nutritive lifestyle. The objective of this work is to carry out an analysis of the market through bibliographic research to understand the evolution and trends of the market in this segment.